PENGARUH CERITA FIKSI TERHADAP BUDAYA LITERASI DI KALANGAN MAHASISWA - Salmaa Ihsania; Wikanengsih Wikanengsih; Mekar Ismayani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is based on the low interest in reading among students. Reading as a core of literacy activities because by reading, other language skills will be mastered by itself. Literacy culture can be enhanced through reading material, one of which is fiction reading books. In other words, everyone has a tendency to like certain genre of books. Fiction can affect literacy culture because it is considered very popular and is popular with students with these factors increasing student reading interest when reading a fiction. The purpose of this study is to describe the influence of fiction on literacy culture. The method used in this study is a quantitative descriptive method that describes data in the form of numbers with calculations through a simple linear regression formula. Data collected through question and questionnaire instruments filled out by students. Completion of questions and questionnaires was conducted on 30 students of Indonesian Language and Literature Education IKIP Siliwangi. The results of the study prove the significance level of 0.02 <0.05, the regression model can be used to predict the participation variable or in other words there is the influence of fiction story variables on literacy culture. It also shows that students tend to like fiction genre books compared to other genres. Therefore, these results prove the influence of fiction in literacy culture.